Help Me Breathe, Please - Dam Eikhof, Karin (Dansk Tidsskrift for Akutmedicin, 2019)
Background: The aim was to gain insight into how patients with chronic obstructive pulmonary disease (COPD) experience being acutely admitted to an emergency department in Denmark. The Department is characterized by a large number of acute patients, which means that the focal point for the healthcare professionals may be to ensure vacant beds. This may be at the expense of caring for the patients sufficiently due to their individual needs. Focus on the flow culture may be contrary to the need for e.g. silence, safety, continuity in care and time with the healthcare professionals. Methods: This study has a qualitative design with a phenomenological hermeneutic approach. The empirics consist of qualitative semi-structured interviews with fourteen patients admitted to an emergency department in Denmark. The data has been analysed through the four steps about meaning condensation and meaning interpretation as described by Kvale and Brinkmann. Results: The preliminary analyses indicated that patients being admitted to the Emergency Department experience a strong need for getting help to breathe and rest. They have struggled with their breathing when they were at home and therefore feel extremely tired. Thus, the chaos that often exists in the Emergency Department may affect the patients’ well-being. In addition, the healthcare professionals’ way of communicating with the patients has a great impact on patient´s feeling safe and comfortable. Conclusion: By focusing on the patients´ individual fundamental care needs in a busy department, it may qualify continuity of care for patients with COPD.